Nonverbal Communication in Cross-Cultural Learning: Insights from a Native Speaker - Rahayu, Pipit; Ouarniki, Ouafa; Silvia, Sulis (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
In today’s multicultural learning environments, effective communication involves more than just spoken language, particularly in Cross-Cultural Understanding (CCU) classes where students from diverse linguistic and cultural backgrounds interact. Despite its importance, nonverbal communication remains an often-overlooked component in educational research. This study aims to explore how a native English speaker utilizes various nonverbal communication strategies—such as body movements, facial expressions, vocalics, proxemics, environmental cues, and communication objects—to enhance interaction and foster understanding in a CCU classroom. Conducted through a qualitative approach, the research involved a purposive sample consisting of one native speaker and twenty non-native students from a university CCU class. Data collection methods included structured classroom observations, video recordings, and field notes, guided by an observation checklist designed to identify specific nonverbal behaviors and their communicative functions. The results reveal that the native speaker effectively employed nonverbal cues to clarify meanings, sustain student engagement, build rapport, and bridge cultural differences. These cues played a vital role in supporting comprehension and promoting a positive learning atmosphere. The findings suggest that nonverbal communication is an essential pedagogical tool in cross-cultural settings, offering valuable insights for educators seeking to enhance intercultural competence and communication efficacy in diverse classrooms.